A Typology of Reasoning in Deliberative Processes: A Study of the 2010 Oregon Citizens' Initiative Review. Issue 2 (2022) - Fischer, Ken; Reedy, Justin; Piercy, Cameron W.; Thapaliya, Rashmi
No abstract available